PRAKIRAAN GELOMBANG PERAIRAN INDONESIA MENGGUNAKAN MODEL GENERASI KETIGA (MODEL WAM) - Hariadi
Abstract: Surface wind data (10 meters) that have been produced by KNMI such as analysis wind data up to 72 hours wind forecast, have been used in this study as primary data for the 3rd generation wave model, WAM in getting the wave parameters. Those are significant wave height, mean period, and wave directions, and also the height, mean period, and direction of the swell that have been occurred in Indonesian and its surrounding waters which stretchs out from I I° N to 15°S and 90°E to 144°E using the grid band of° latitude x % ° longitude. This study was carried out in order to understand the usefulness of the deep-water model for ocean state forecasting within Indonesian region. It was done by studying the model capability in responding the wind input to produce the spreading wave parameters distribution while the ocean condition is influenced by westerlies (analysis wind data of 1-10 February 2000, analysis wind data and forecasting of 5 February 2000) and influenced by easterlies (analysis wind data of 21-29 May 2000, analysis and forecasting wind data 19 May 2000). The results of the model were pictured by the map of wave distributions using Arc View GIS. Furthermore, they had been evaluated qualitatively using Topex/Poseidon satellite data, and later on compared qualitatively to the results of MRI II and NWW III model. Result of evaluation show that the WAM model generally has produced similar wave pattern with satellite data and the results of the other models. The difference in wave height lies in the order that could be tolerated The wave condition calculated by the model in Indonesian waters in February 2000, gave the maximum wave height in South China Sea where ocean condition is influenced by the westerlies. The wave computed height is up to 3 meters with period of 5-6 second and moving to the south. In May 2000, the maximum wave height occurred in Indian Ocean south of Timor Island where the ocean condition is influenced by the easterlies . The wave height is up to 2.5 m with period of 5-6 seconds and moving to the east.